Mechanical behavior of HTCE propellant: Dependence on strain rate and temperature - Cong Zhu; Wenhao Liu; Wu Yang; Teng Wang; Mengjing An; Yunjun Luo (Polymer Testing)
High-solid-content polymer composites such as solid propellants are widely used in different fields. Although the proportion of polymer components in the material is relatively low, the mechanical influence of polymers on composite materials is crucial. The mechanical response of the materials is highly rate and temperature dependent. This study aims to investigate the effects of strain rate and temperature on the uniaxial tensile properties of HTCE propellant. To this end, an HTCE propellant with a specific composition was prepared, and its tensile behaviour and cyclic softening characteristics were examined under strain rates ranging from 0.00104 s−1 to 0.10417 s−1. The results demonstrate that HTCE propellant exhibits a highly nonlinear stress-strain relationship and high dewetting performance. With increasing strain rate, the ultimate tensile stress, strain, failure strain and stress all show varying degrees of enhancement. Also, they exhibit a positively correlated exponential function relationship with engineering strain. Furthermore, uniaxial tensile tests conducted at temperatures ranging from 233.15 K to 343.15 K reveal that the mechanical properties of HTCE propellant are significantly improved at lower temperatures. At last, a computational constitutive model about CSED(cumulative strain energy density) and ε is presented in a manner consistent with experiment data.